Atypical Demonstratives Syntax, Semantics and Pragmatics - Coniglio, Marco; Murphy, Andrew; Schlachter, Eva; Veenstra, Tonjes (Linguistische Arbeiten (Max Niemeyer Verlag) ;, 2018)
Atypical demonstratives have not received adequate attention in the literature so far, or have even been completely neglected. By providing fresh insights and discussing new facets, this volume contributes to the better understanding of this group of words, starting from specific empirical phenomena, and advances our knowledge of the various properties of demonstratives, their syntactic multi-functionality, semantic feature specifications and pragmatic functions. In addition, some of the papers discuss different grammaticalization processes involving demonstratives, in particular how and from which lexical and morphosyntactic categories they originate cross-linguistically, and which semantic or pragmatic mechanisms play which role in their emergence. As such, the different contributions guide the readers on an adventurous journey into the realm of different exotic species of demonstratives, whose peculiar properties offer new exiting insights into the complex nature of demonstrative expressions themselves.